Vanadium dioxide for thermochromic smart windows in ambient conditions. (September 2021) - Shen, Nan; Chen, Shi; Huang, Runqing; Huang, Jiaqi; Li, Jingyi; Shi, Run; Niu, Shuzhang; Amini, Abbas; Cheng, Chun
Abstract: Smart windows have attracted increasing attentions in recent decades because of their ability to automatically regulate indoor solar irradiation, reduce the energy consumption of air-conditioning, and maintain comfortable thermal environment for indoors. As a typical thermochromic material, vanadium dioxide (VO2) exhibits reversible metal-insulator transition accompanied with dramatic optical transmittance changes near the room temperature, which makes VO2 -based smart windows promising for practical uses in ambient conditions. This review summarizes recent advancements of techniques utilized for tailoring the properties of VO2 to meet the specific requirements for smart windows. The phase transition temperature (Tc ) should be reduced approaching the room temperature, whereas luminous transmittance (Tlum ) and solar energy modulation efficiency (ΔTsol ) must be high enough to capture adequate daylight and perform with an energy-saving trend. The doping strategy and integrating with functional coatings can regulate the properties of VO2 films. Besides the passive response to ambient temperature, electrothermal techniques and integration with specific materials, which generate heat, can enable VO2 to work with improved optical properties regardless of its higher Tc than the room temperature. Future maps for the development of VO2 films are provided in the last part of the review. Graphical abstract: Image 1 Highlights: The methods used to improve thermochromic performance of vanadium dioxide (VO2 ) films for smart window applications are discussed in detail. The doping strategy to modify the performance of VO2 is carefully presented. The electrothermal technique and integrated structures with different functional materials are explored. The challenges and opportunities of VO2 -based smart windows are summarized.